PENGEMBANGAN PERANGKAT PEMBELAJARAN KOMPETENSI CNC PLASMA CUTTING DI PRODI PENDIDIKAN TEKNIK MESIN - Muhammad Fikri Haikal Aida Rafiq; Yuyun Estriyanto; Taufik Wisnu Saputra (Nozel : Jurnal Pendididikan Teknik Mesin, 2025)
The CNC Plasma Cutting course is an elective course for mechanical engineering education students who have an interest in deepening their knowledge in welding and cutting using machines with computer technology. The CNC Plasma Cutting practical learning that is currently being carried out is considered not optimal, because the product produced is only a sample. The aim of this research is to: Develop learning tools using practicum modules to meet the learning needs of the CNC Plasma Cutting course in the PTM FKIP UNS Study Program. The method used in this research is development using the ADDIE (Analysis-Design-Develop-Implement-Evaluate) model. The data source comes from students. This development research uses questionnaire data collection techniques. A questionnaire is a written data collection technique. This data collection was carried out to analyze needs and the module evaluation stage. The data obtained from this questionnaire is used as a reference for improving the practicum module being developed. The data analysis technique used is explained as follows. The quantitative data analysis technique in the CNC Plasma Cutting practicum module that was developed was obtained from student assessments. The questionnaire given to students was a closed questionnaire using a Likert scale. The Likert scale is used to measure students' opinions or assessments. Based on the results of the research that has been carried out, it can be concluded that the development of a CNC Plasma Cutting practicum module is very necessary to improve the quality of student learning. The needs analysis shows that this module provides clear structure and guidance, makes it easier for students to take part in practicums, and provides references that can be accessed at any time. The project-based learning method used in this module has succeeded in improving students' practical skills through real projects.